A Holistic Review of MSME Entrepreneurship in Indonesia: The Role of Innovation, Sustainability, and the Impact of Digital Transformation - Judijanto, Loso; Utami, Eva Yuniarti; Apriliani, Diah; Rijal, Syamsu (International Journal of Business, Law, and Education, 2024)
This study conducts a comprehensive examination of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, focusing on their role in the economy, challenges in innovation, sustainability, and digital transformation. With over 97% of the local labor force employed by MSMEs, their significance is undeniable. However, obstacles, exacerbated by the COVID-19 pandemic, include a financing gap, innovation difficulties, and limited resources hindering digitalization. The research, based on a sample of 250 MSMEs, utilizes Partial Least Square-Structural Equation Modeling (PLS-SEM) to reveal the positive and significant impact of innovation, sustainability, and digital transformation on MSME entrepreneurship. Practical implications suggest prioritizing innovation, integrating sustainable practices, and recognizing the importance of digitalization for MSMEs’ success, with broader implications for socio-economic and environmental goals.